The Study Abroad Diamond: Examining the Facets of Supporting Student Mobility (Comparative & International Education Series, 2021)
A challenge confronting institutions of higher education is how to produce graduates that have the knowledge, skills, and dispositions to work with diverse populations and to participate in a pluralistic, interconnected world. In particular, colleges of education are under pressure to produce global-ready teachers. Within this context, there has been increasing support for student mobility in terms of greater participation in diverse locales; including international teaching opportunities. One method to achieve this goal, and to increase student mobility, is to provide opportunities for study abroad experiences that place candidates in international field experiences. Our chapter describes and examines three case studies of developing and implementing study abroad programs focused on providing international teaching experiences for teacher candidates at a large, research university in the Southeast region of the United States.